Pemberdayaan Ekonomi Berbasis Usaha Mikro Melalui Bankziska (Studi Kasus: Pengelolaan Dana Lazismu Kabupaten Mojokerto) - Iwantoro Iwantoro; Moh. Nurhakim (Jurnal Pemberdayaan Masyarakat, 2022)
This study aims to describe the systematics of providing assistance through Bankziska to micro-enterprises and how useful the aid program is to help develop/empower the economy of micro-enterprises in Mojokerto. This research uses a qualitative approach with the type of case study research, data collection procedures using non-participant observation, interviews, and documentation. Informants as the primary data source consisted of the chairman of Lazismu, the director of Bankziska, and Bankziska's partners. Technical data analysis with data reduction, data presentation, and drawing conclusions. To test the validity of the data used triangulation technique. This study found the following results: (1) the scheme of providing business capital assistance/loans through two stages, the first stage the partners were given a loan of Rp. 500,000.00 while the second stage after the partner pays off the first loan a maximum of Rp. 1,000,000.00 (2) the usefulness of the Bankziska program in the economic development/empowerment of micro business actors (partners) is very significant. In addition to this program is able to reduce dependence on moneylenders, it is also able to assist in business capital although on a small scale.